PROSES KOMUNIKASI PADA FENOMENA IMITASI REMAJA DI KOMUNITAS KPOPERS BATAM - Diana, Dina; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2019)
The purpose of this study was to determine the communication process of behavior change that occurred in Batam kpopers adolescents and the role of the media in the communication process related to imitation behavior changes in Batam kpopers adolescents. This study uses descriptive qualitative method using Miles & Huberman data analysis, in determining informants, researchers used purposive sampling technique and the informant consisted of members of the KPOP-like community in Batam. Primary data and secondary data that researchers use are in-depth interviews, documentation, nonparticipant observations and articles from the internet. The results showed that teenagers affected by the phenomenon of imitation of the Korean Wave gave some behavioral changes to teenagers who like kpop. The behavioral changes that occur are imitating their idols, from the behavior of their idols like the habits of the idols they see through video, fashion, to learning and using Korean in their daily lives, such changes occur in: (1) the process of attention, (2) the process of remembrance, (3) the process of motor reproduction and (4) motivation.